Administering analgesia sublingually is a suitable option for children with acute abdominal pain in the emergency department. (17th August 2018) - Cozzi, Giorgio; Zanchi, Chiara; Chiaretti, Antonio; Tipo, Vincenzo; Cernich, Marta; D'Anna, Carolina; Fantacci, Claudia; Conversano, Ester; Zanon, Davide; Ronfani, Luca; Barbi, Egidio
Abstract: Aim: Acute abdominal pain is a frequent complaint in children attending emergency departments. The aim of this study was to investigate the pain score reductions when children with acute abdominal pain received medication sublingually. Methods: We carried out a multicentre randomised controlled trial in three children's hospitals in Italy between March 2015 and June 2017. Children from four to 18 years of age with acute abdominal pain were recruited if their self‐reported pain was at least six on a scale from 0–10. The children were randomised to receive ketorolac 0.5 mg/kg (n = 70) or tramadol 2 mg/kg (n = 70) sublingually or a melt in the mouth powder of 20 mg/kg paracetamol (n = 70). The main study outcome was the pain scores for the three drugs after two hours. Results: The 210 children (58.6% girls) had a median age of 12 years with an interquartile range of 9–14.3. The median pain scores at two hours were not significantly different between ketorolac 2.0 (interquartile ranges, IQR 0.0–4.3) and tramadol 3.0 (IQR 1.0–5.0) vs paracetamol 3.0 (IQR 0.8–5.0). The median pain reductions were all 5.0 points. Conclusion: Delivering analgesia sublingually was a suitable option for pain relief in children with acute abdominal pain in the emergency department.